A Pathway to Fabricate Hollow Fiber Membranes with Isoporous Inner Surface. Issue 7 (30th January 2017) - Sankhala, Kirti; Koll, Joachim; Radjabian, Maryam; Handge, Ulrich A.; Abetz, Volker
Abstract : A novel inside isoporous hollow fiber membrane is prepared using the dry‐jet wet spinning technique. Subsequently, the self‐assembly of block copolymer in combination with nonsolvent‐induced phase separation takes place in the lumen side of the spun hollow fibers with a diameter of less than 1 mm leading to technologically favored inside membranes for water purification.